The sabermetric revolution : assessing the growth of analytics in baseball - Baumer, Benjamin; Zimbalist, Andrew S. (Philadelphia : University of Pennsylvania Press, 2014)
Explores the history of statistical analysis in baseball, how it can best be used today, and how it must evolve for the future.
Revisiting Moneyball -- The growth and application of baseball analytics today -- An overview of current sabermetric thought I: Offense -- An overview of current sabermetric thought II: Defense, WAR, and strategy -- The Moneyball diaspora -- Analytics and the business of baseball -- Estimating the impact of sabermetrics -- Appendix: The expected run matrix -- Modeling the effectiveness of sabermetric statistics -- Modeling the shifting inefficiencies in MLB labor markets.
Includes bibliographical references and index.
Keywords: Baseball -- Statistical methods; Baseball -- Mathematical models